If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 378 = 6 + -6(8b + -6) Reorder the terms: 378 = 6 + -6(-6 + 8b) 378 = 6 + (-6 * -6 + 8b * -6) 378 = 6 + (36 + -48b) Combine like terms: 6 + 36 = 42 378 = 42 + -48b Solving 378 = 42 + -48b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '48b' to each side of the equation. 378 + 48b = 42 + -48b + 48b Combine like terms: -48b + 48b = 0 378 + 48b = 42 + 0 378 + 48b = 42 Add '-378' to each side of the equation. 378 + -378 + 48b = 42 + -378 Combine like terms: 378 + -378 = 0 0 + 48b = 42 + -378 48b = 42 + -378 Combine like terms: 42 + -378 = -336 48b = -336 Divide each side by '48'. b = -7 Simplifying b = -7
| (4a+5)(4a+5)(4a+5)= | | -6.1a=74.42 | | -9.3=g-1.7 | | =x^2-10x+425 | | /2+x/5=1 | | 16x^4-16x^2+3=0 | | 3x+5=-2(x-5) | | 8r^2+23r=36 | | 9=-2-y | | 34x-13=55 | | 16a+2b=4 | | -15=5m^2+28m | | Y=8x^2+2x-3 | | -1x+3=-8 | | n+n+1+n+2=54 | | -6-2x=10-8 | | .25x+8=.62x+2 | | 15/(8n-32) | | 11x-33=8x+0 | | 2x^2-7x-70=3x | | 5p+2=4p-9 | | (-18)+q=5 | | 2t^2+5=2t^2+1 | | n+n+1+n+1=54 | | 15/8n-32 | | -5.9=k/3 | | 25m^2+2=3 | | 7-3x=5x+14 | | 10x-50=25 | | 3x-6x^2/x^3 | | x*0.65=28748 | | 100-38= |